The relationship between length and active force for submaximal skeletal muscle contractions: a review - Zimmermann, H. B.; Macintosh, B. R.; Pupo, J. D. (Sports Medicine, 2024)
The force-length relationship is usually obtained for isometric contractions with maximal activation, but less is known about how sarcomere length affects force during submaximal activation. During submaximal activation, length-dependent alterations in calcium sensitivity, owing to changes in cross-bridge kinetics (rate of attachment and/or detachment), result in an activation-dependent shift in optimal length to longer sarcomere lengths. It is known that sarcomere length, as well as temperature and phosphorylation of the regulatory light chains of myosin, can modify Ca2? sensitivity by altering the probability of cross-bridge interaction. This altered calcium sensitivity is particularly important for submaximal force levels, as it can change the shape of the length dependence of force, with peak force occurring at sarcomere lengths longer than those associated with maximal filament overlap. In athletic contexts, contractions typically do not reach maximal intensity. Therefore, understanding that the ability to produce force under both maximal and submaximal conditions can differ, and that peak force can be generated at different lengths, could influence the development of targeted training regimens optimal for each sport.